Transient-based identification of wireless sensor nodes - Danev, Boris; Capkun, Srdjan (2009 International Conference on Information Processing in Sensor Networks, 2009)
Identification of wireless sensor nodes based on the characteristics of their radio transmissions can provide an additional layer of security in all-wireless multi-hop sensor networks. Reliable identification can be means for the detection and/or prevention of wormhole, Sybil and replication attacks, and can complement cryptographic message authentication protocols. In this paper, we investigate the feasibility of transient-based identification of CC2420 wireless sensor nodes. We propose a new technique for transient-based identification and show that it enables reliable and accurate sensor node recognition with an Equal Error Rate as low as 0.0024 (0.24%). We investigate the performance of our technique in terms of parameters such as distance, antenna polarization and voltage and analyze how these parameters affect the recognition accuracy. Finally, we study the feasibility of certain types of impersonation attacks on the proposed technique.